Mast cells modulate the inflammatory process in endotoxin-induced uveitis - Silva, Pierre Sebastiao da; Girol, Ana Paula [UNESP]; Oliani, Sonia M. [UNESP] (Molecular Vision, 2011)
Purpose: To investigate the role of mast cells and annexin-A1 (Anxa1) in endotoxin-induced uveitis (EIU). Methods: EIU was induced by injection of lipopolysaccharide (LPS) into the paws of rats, which were then sacrificed after 24 and 48 h. To assess EIU in the absence of mast cells, groups of animals were pretreated with compound 48/80 (c48/80) and sacrificed after 24 h after no treatment or EIU induction. The eyes were used for histological studies and the aqueous humor (AqH) pool was used for the analysis of transmigrated cells and Anxa1 levels. In inflammatory cells, Anxa1 expression was monitored by immunohistochemistry. Results: After 24 h, rats with EIU exhibited degranulated mast cells, associated with elevated numbers of infiltrating leukocytes and the high expression of Anxa1 in the AqH and the neutrophils. After 48 h of EIU, the mast cells were intact, indicating granule re-synthesis, and there was a reduction of neutrophil transmigration and an increase in the number of mononuclear phagocytic cells in ocular tissues. Anxa1 expression was decreased in neutrophils but increased in mononuclear phagocytic cells. In the animals pretreated with c48/80 and subjected to EIU, mast cells responded to this secretagogue by degranulating and few transmigrated neutrophils were observed. Conclustions: We report that mast cells are a potential source of pharmacological mediators that are strongly linked to the pathophysiology of EIU, and the endogenous protein Anxa1 is a mediator in the homeostasis of the inflammatory process with anti-migratory effects on leukocytes, which supports further studies of this protein as an innovative therapy for uveitis.